(untitled) (Biological Sciences - PJSIR, 1999)
This paperdealswithchangesinmuscularactivityoCgastrocnemiusmuscleof Uromastix liardwickii Correptilianbuffer havingdifferentconcentrationofKCI.Contractiontime,half relaxationlime,peakdurationtime,maximumrateof rise01" tensionandisotonictensionhavebeenselectedastheparametersforevaluationofmusclecontractionperformance.These studiesconfirmthat,maintenanceofK iontothenormalvaluebothintheextraandintracellularl1uidisnecessary,because itsdecreaseandincreasefrom thenormalvalueisdangerousforlife.